An Allostatic Theory of Oxytocin. Issue 7 (July 2020) - Quintana, Daniel S.; Guastella, Adam J.
Abstract : Oxytocin has garnered considerable interest for its role in social behavior, as well as for the potential of intranasal administration to treat social difficulties. However, current theoretical models for the role of oxytocin in social behavior pay little consideration to its evolutionary and developmental history. This article aims to broaden our understanding of the role of oxytocin in social behavior by adopting an ethological approach through the lens of Nikolaas Tinbergen's 'four questions' – how does oxytocin work; how does the role of oxytocin change during development; how does oxytocin enhance survival; and how did the oxytocin system evolve? We argue that oxytocin is most accurately described as an allostatic hormone that modulates both social and non-social behavior by maintaining stability through changing environments. Highlights: Several studies on oxytocin could not be replicated, and this has been attributed to methodological limitations. Although this is an important issue, the impact of the lack of an overarching theory has yet to be recognized. Oxytocin is conventionally considered to be a social hormone, but more recent work suggests that it also modulates non-social cognition and behavior. Oxytocin-like peptides in evolutionarily ancient organisms regulate allostatic processes, such as osmoregulation, that are conserved in humans. Oxytocin facilitates the processing of social and non-social sensory cues that are crucial for survival. Oxytocin receptor location and oxytocin release patterns govern the diverse but coordinated actions of oxytocin on physiology and behavior. Oxytocin signaling changes across development to support the different environmental pressures at each developmental stage.